We Do Not Like It: A Likert-Type Scale Survey on the Attitudes of a Young Population towards the Transhumanistic Theory of Education - Adamczak, Zuzanna; Agacinska, Julia; Bialecka, Oliwia; Bogacz, Urszula; Carewicz, Kinga; Chudy, Oliwia; Fiebig, Katarzyna; Fiszgala, Olga; Frackowiak, Beata; Frackowiak, Joanna; Frackowiak, Marika; Gizycka, Karolina; et al. (My University, 2018)
Transhumanists assume that future education may be purely based on technological stimulation. The question is: Do potential clients of education “like” such vision? In order to check this, we asked over one thousand two hundred young Poles to evaluate their identification with the transhumanistic theory of education. The results are quite surprising: its show that they disagree with the assumptions of this theory, while they rather agree with the postulates of more traditional (and no technology-based) concepts of education.
Keywords: transhumanism; large population-based studies; cyborgs; young generation